TWO CONCEPTIONS OF LIBERALISM: Theology, Creation, and Politics in the Thought of Immanuel Kant and Edmund Burke1 - Insole, Christopher J. (Journal of religious ethics, 2008)
Constitutional liberal practices are capable of being normatively grounded by a number of different metaphysical positions. Kant provides one such grounding, in terms of the autonomously derived moral law. I argue that the work of Edmund Burke provides a resource for an alternative construal of constitutional liberalism, compatible with, and illumined by, a broadly Thomistic natural law worldview. I contrast Burke's treatment of the relationship between truth and cognition, prudence and rights, with that of his contemporary, Kant. We find that in each case where Kant's system is constructed from the first principle of autonomy, Burke's thought is oriented toward an end that is not of our making. Readings of Burke as a natural law thinker are currently out of fashion among Burke commentators; without relying, for the main thesis, on historical claims about Burke's “Thomism,” I nonetheless explore and challenge some of the assumptions that underlie the current orthodoxy.